The effect of reflexotherapy on chemotherapy-induced vomiting of - Yoosefian Miandoab, Nazanin; Ezzati, Zhaleh; Arbabi, Farshid; Manoochehri, Hooman; Zayeri, Farid (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim Vomiting as a side effect of chemotherapy causes to refuse or delay in treatment by most cases. Nowadays, for controlling these side effects researchers attempt to use noninvasive-, safe- and low cost methods, instead of expensive drugs with various side effects. This study aimed to assess effect of reflexotherapy on vomiting reduction among patients under chemotherapy, in oncology-hematology ward of Zahedan's Ali Ebn Abitaleb Hospital in 2010. Materials and Methods This study was a before and after clinical trial (pre-test and post-test) with a group of 37 patients. The participants were selected using purposeful sampling method and based on the results of a pilot study. They were also considered once in the control group (receiving anti-vomiting drug Granisetron) and after 15 to 20 days in the interventional group (receiving reflexotherapy in a period of 10 minutes for each leg). The Summary of Morrow Questionnaire and CTCv 2.0 Y/WX Findings The mean age of samples was 44.73 ±13.38 (years). Majority of participants were married and women. Patients were in their second to 15th cycle of chemotherapy; receiving Cisplatin–Gemzar or Adriamycincyclophosphamide and were from breast cancer cases. Assessment of severity of vomiting during first 24 hours showed more sever vomiting in the first 4 hours among control group than interventional group (p<0.001), but it was more severe in interventional gropup than control group in third 4 hours (p<0.001) and the second 12 hours (p=0.006). During the second 4 hours, severity of vomiting was not significantly different between the two Groups (p=0.313). Finnally, the results showed no significant difference between two treatment methods respecting their effect on severity (p=0.153) and the number of vomiting (p=0.239) during the 24 hours after treatment. Conclusion Although reflexotherapy was not shown to have positive effect on chemotherapy induced vomiting of patients but it caused to reduce severity and number of vomiting in the first 4 hours after chemotherapy among patients with moderate and sever vomiting. Therefore, experimental study using reflexotherapy is recommended in multiple sessions. Key words: Chemotherapy, Vomiting, Reflexotherapy. REFERENCES -Akbari ME et al (2009). [Iran Cancer Report]. 1 st edition. Tehran, Darolfekr Publishing. (Persian). -Azadeh P et al (2006). Granisetron effects on ECG in cancer patients receiving chemotherapy. Pejouhandeh Journal, Shahid Beheshti University of Medical Sciences. 11 (4) 241-244. (Persian). -Black JM Hawks JH (2009) Medical-Surgical Nursing: Clinical Management for Positive Outcomes: 7 th edition. USA, Saunders. -Blunt E (2006). Foot reflexology. Holistic Nursing Practice. 20 (5) 257-259. -British Reflexology Association (2009). [On line] http: // www. Britreflex. Co.uk. htm [12 Dec. 2009]. -Cady RF (2009) Legal issues related to complementary and alternative medicine. Journal of Nursing Administration Healthcare Law, Ethics and Regulation. 11 (2) 46-51. -Chainakin P (2006) Effects of hand reflexology on nausea, retching and vomiting in cancer patients receiving chemotherapy. (dissertation). M. N. S (Adult Nursing).Thailand: Mahidol University. -Donnerer J (2003).Antiemetic Therapy. 1 th edition. London, Karger publishing. -Donovan Monahan F et al (2007). Phipps' Medical-Surgical Nursing Health and Illness Perspectives. 8 th edition. Philadelphia, Lippincott Publishing. -Elahi F et al (2005). [Drugtherapy in Oncology].1 st edition. Tehran, Hamgenan Publishing. (Persian). -Eliopoulos C (1999). Integrating Conventional and Alternative Therapies:holistic care of chronic conditions. Missouri, Mosby publishing. -Farahani B Safavi M Salehi S (2006). [Evaluating the effect of instructing patient care on knowledge, attitude and performance of the attentives of cancer patients under chemotherapy referring to the University Hospitals of Tehran University of Medical Science]. Medical Science Journal of Islamic Azad University Tehran Medical Branch. 14 (2) 99- 103. (Persian). -Filshie J Rubens CNJ (2006). Complementary and alternative medicine. Anesthesiology Clinics of North America. 24 (1) 81-111. -Food and Drug Administration 2009. [On line] http://www. Fda.gov/Drugs/default. Htm [6 Feb. 2009]. -Glass E Cluxton D Rancour P (2006). Principles of Patient and Family Assessment, Ferrell BR and Coyle N (Eds) Textbook of Palliative Nursing. 2 th edition. New York, Oxford University Press. -Gralla JR Grunberg SM Messner C (2009). Booklet of Understanding and Managing Chemotherapy Side Effects. [Online]. Available at: <http:www.cancercare.org>. [3 Dec 2009]. -Hodgson H (2000) Does reflexology impact on cancer patient's quality of life? Nursing Standard. 14 (31) 33-38 -Helms R Quan JD (2006). Textbook of Therapeutics: Drugs and Disease Management. 8 th edition.Baltimore, Lippincott Williams and Wilkins. -Kohara H et al (2004). Combined modality treatment of aromatherapy, footsoak and reflexology relieves fatigue in patients with cancer. Journal of Palliative Medicine. 7 (6) 791-796. -Kris MG (2003). Why do we need another antiemetic? Journal of Clinical Oncology. 21 (22) 4077-4080. -Lett A (2000). Reflex Zone Therapy for Health Professionals. 1 th edition. London, Churehill Livingstone publishing. -Moosavizadeh K Ansari H (2008). [Alternative/complementary medicine and medical education]. Payesh, Journal of the Iranian Institute for Health Sciences Research. 7 (4) 329-336. 2009. -National Cancer Institute (A) 2009. [On line] http: // www. cancer.gov/cancertopics/treatment/druginfo. htm [7 Feb 2009]. -National Cancer Institute (B) 2009 .[on line] http: // www. cancer.gov/ProtocolDevelopment/electronic_applications/ctc.htm [7 Feb 2009]. -Patient-Reported Outcome and Quality of Life Instruments Database 2009. [online]http://www.proqolid.org/instruments/morrow_assessment_of_nausea_and_emesis_mane [9 Feb 2009]. -Rick S (2007). [The Reflexology Work out]. 2 nd edition. Translated by: Yousefi.B .Tehran, Elm and Harekat Publishing. (Persian). -Rivaz M et al (2005). [Efficacy of transcutaneous electrical nerve stimulation in the control of nausea and vomiting in patients undergoing chemotherapy]. Journal of Medical Research of Shiraz University of Medical Sciences. 3 (2) 47-55. (Persian). -Ross CS et al (2002). A pilot study to evaluate the effect of reflexology on mood and symptom rating of advanced cancer patients. Palliative Medicine. 16 (6) 544-545. -Sajadian A et al (2005). [The use of complementary medicine in cancer patients]. Payesh, Journal of the Iranian Institute for Health Sciences Research. 4 (3) 197-205. (Persian). -Smeltzer SC Brunner L Suddarth D (2008). Textbook of Medical-Surgical Nursing (cancer). R1st edition. Translated by :Hosseinzadeh.M . Tehran, Boshra Publishing. (Persian). -Sok SR Erlen JA Kim KB (2004). Complementary and alternative therapies in nursing curricula : A new direction for nurse educators. Journal of Nursing Education. 43 (9) 401-405. -Weiss R (2006). [Massage Therapy]. 1 st edition. Translated by: Golchin.M. Tehran, Shahrab and Ayandehsazan publishing. (Persian). -Wesa K Gubili J Cassileth B (2008). Integrative oncology: complementary therapies for cancer survivors. Hematology/Oncology Clinics of North America. 22 (2) 343-353. -Won JS Jeong IS Kim JS (2002). Effect of foot reflexology on vital signs, fatigue and mood in cancer patients receiving chemotherapy. Journal of Korean Academy of Fundamentals of Nursing. 9 (1) 16-26. -World Health Organization (2009). [On line] http: // www. Who.int/features/qa/15/en/index.htm [5 Feb 2009]. -Xavier R (2007) Facts on refexology (Foot Massage). Nursing Journal of India. 98 (1) 11-12. -Yahyavi SH Nazari L (2006). [Role of haloperidol in managing gynecologic-related postoperative nausea and vomiting]. Medical Science Journal of Islamic Azad University Tehran medical branch. 15 (1) 9-13. (Persian). -Yang JH (2009). The effects of foot reflexology on nausea, vomiting and fatigue of breast cancer patients undergoing chemotherapy". [Abstract]. Available at : http : // www.ncbi.nlm.nih.gov/pubmed/15778569.htm. Accessed: 7 Feb. -Zeighami Mohammadi Sh et al (2008). [Quality of life in cancer patients undergoing chemotherapy]. Scientific Journal of Hamadan Nursing and Midwifery Faculty. 16 (1) 5-10. (Persian). ) was confirmed beforehand. Data was analyzed using central and dispersion indexes as well as Wilcoxon and Mann-Whitney tests and Marginal modeling (generalized estimating equations GEE). (Common Toxicity Criteria Version 2) of National Cancer Institute of America were used for making a questionnaire to data collection. Face and content validity of questionnaire and its reliability (Chronbach alpha Coefficient =